Pengaruh Konsentrasi Enzim, Ragi, dan Lama Fermentasi terhadap Pembuatan Bioetanol Berbahan Baku Chlorella pyrenoidosa - Jannah, Asyeni Miftahul; Wahyuni, Indah; Amalia, Renanda; Savrinda, Cynthia; Hani, Indry Permata (Jurnal Teknik Kimia USU, 2024)
The demand for energy is inversely proportional to the current amount of energy in Indonesia. In order to face this problem, it is necessary to develop renewable energy sources. This study was conducted to analyze enzymes effect in the Chlorella pyrenoidosa hydrolysis, analyze yeast effect and the fermentation time of Chlorella pyrenoidosa on the bioethanol produced. The variables used are variation of Î±-amylase enzyme concentration of 25%, 35%, 45% (v/w), and variation of yeast concentration of 5%, 10%, 15% (w/v) and fermentation time of 7, 9, 11 days. From the analysis conducted, the highest glucose content was 13.119%, which was in the variation of 45% (v/w) Î±-amylase enzyme concentration. The amount of enzyme concentration used was in accordance with glucose production. The highest bioethanol was obtained with a sample involving 10% (v/b) yeast fermented for 9 days, which amounted to 27%.